2022
DOI: 10.1186/s12887-022-03391-2
|View full text |Cite
|
Sign up to set email alerts
|

What is the state of children’s participation in qualitative research on health interventions?: a scoping study

Abstract: Background Children are the focus of numerous health interventions throughout the world, yet the extent of children’s meaningful participation in research that informs the adaptation, implementation, and evaluation of health interventions is not known. We examine the type, extent, and meaningfulness of children’s participation in research in qualitative health intervention research. Method A scoping study was conducted of qualitative published rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…However, for this to occur meaningfully, research teams need to commit to training children in an age-appropriate way, similar to how research assistants are equipped with the skills that they need to engage deeply with the project. The reflective guide developed by Hunleth et al is one tool that may assist researchers who wish to deepen the meaningfulness of children’s participation in health research [ 96 ]. Although this preparation may require more time and resources, it will ultimately build children’s capacity that can be engaged in future research projects and ensuring that research aims are aligned with needs prioritized by children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, for this to occur meaningfully, research teams need to commit to training children in an age-appropriate way, similar to how research assistants are equipped with the skills that they need to engage deeply with the project. The reflective guide developed by Hunleth et al is one tool that may assist researchers who wish to deepen the meaningfulness of children’s participation in health research [ 96 ]. Although this preparation may require more time and resources, it will ultimately build children’s capacity that can be engaged in future research projects and ensuring that research aims are aligned with needs prioritized by children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Hunleth, Spray, Meehan, Lang, and Njelesani [ 1 ] advocated that the cornerstone of children’s meaningful participation is listening without tokenising or diminishing their perspectives and experiences. Their recent scoping study found that children’s meaningful participation in health research has not increased with time [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hunleth, Spray, Meehan, Lang, and Njelesani [ 1 ] advocated that the cornerstone of children’s meaningful participation is listening without tokenising or diminishing their perspectives and experiences. Their recent scoping study found that children’s meaningful participation in health research has not increased with time [ 1 ]. Previous NZ research flags implications for decision-makers, such as local councils and planners, regarding knowledge gained through urban environment research with children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations